Spectrum of hollow visceral injury due to isolated blunt trauma abdomen presented in tertiary care trauma hospital of Pakistan - Ammar , Ahmed Siddique; Hadi, Ali; Anwar, Umbreen; Nawaz, Hassan; Batool, Sana; Naqi, Syed Asghar (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the spectrum of isolated hollow visceral perforations in patients presenting with abdominal blunt trauma. Method: The observational, analytical, cross-sectional study was conducted at the surgical ward of Mayo Hospital, Lahore, Pakistan from July 1, 2020, to June 31, 2021, and comprised patients who presented in the emergency department after blunt trauma to abdomen without any open wound. Findings of hollow visceral injury were confirmed on exploration laparotomy. Data was analysed using SPSS 26. Results: Of the 216 patients, 173(80.9%) were male and 43(19.9%) were female. The overall mean age was 42±9.7 years. Most of the blunt trauma abdomen cases were caused by motor vehicle accidents 59(27.3%). The most common hollow viscus affected was jejunum 42(19.4%), followed by transverse colon 29(13.4%). The most common type of injury observed was single complete disruption of hollow viscus 74(34.2%). Conclusion: The most common hollow organ affected by blunt trauma to the abdomen was jejunum, followed by transverse colon, and motor vehicle accidents were the major cause of these injuries. Key Words: Blunt trauma abdomen, Hollow viscera, Perforation, Motor vehicles, Peritonitis, Tertiary care hospital.